ELECTRONIC SYSTEM OF ORGANIZING AND MANAGEMENT OF STUDENTS' QUALIFICATION PRACTICE - Avezov Mardonbek Abdullayevich (Web of Journals Publishing, 2023)
This article examines pedagogical practice, the tasks of pedagogical practice of students, methods and tools, the quality and effectiveness of the educational process, mobile education, the creation of mobile applications and the possibilities of their use during the internship period.
Keywords: pedagogical practice, mobile education, mobile applications, Android Studio.